Abortion Around the World An Overview of Legislation, Measures, Trends, and Consequences. - GUILLAUME, Agnès; ROSSIER, Clémentine (Population (1634-2941), 2018)
Following the May 2018 Irish referendum largely in favour of abortion, only two European countries, Malta and Andorra, still do not give women the right to decide to end a pregnancy in the first weeks. Outside of Europe, the situations are highly diverse, but abortion remains illegal or restricted to certain conditions in a great number of countries, notably those of the South. This situation not only runs counter to the right of each woman to control her own body but contradicts other internationally recognized rights, such as the rights to equality, health, and free and responsible decision on the number and spacing of children. This "Overview of a Population Question" offers a vast panorama of the issues surrounding abortion, the difficulties in measurement, and the solutions to address them. It reviews current legislation, the most recent data on abortion frequency and methods, as well as the consequences of abortion on women's health and lives.